Prevalence of Depressive Episodes With Psychotic Features in the General Population - Ohayon, Maurice M.; Schatzberg, Alan F. (The American journal of psychiatry, 2002)
OBJECTIVE: The study evaluated the prevalence of major depressive episodes with psychotic features in the general population and sought to determine which depressive symptoms are most frequently associated with psychotic features. METHOD: The sample was composed of 18,980 subjects aged 15-100 years who were representative of the general populations of the United Kingdom, Germany, Italy, Portugal, and Spain. The participants were interviewed by telephone by using the Sleep-EVAL system. The questionnaire included a series of questions about depressive disorders, delusions, and hallucinations. RESULTS: Overall, 16.5% of the sample reported at least one depressive symptom at the time of the interview. Among these subjects, 12.5% had either delusions or hallucinations. More than 10% of the subjects who reported feelings of worthlessness or guilt and suicidal thoughts also had delusions. Feelings of worthlessness or guilt were also associated with high rates of hallucinations (9.7%) and combinations of hallucinations and delusions (4.5%). The current prevalence of major depressive episode with psychotic features was 0.4% (95% CI=0.35%-0.54%), and the prevalence of a current major depressive episode without psychotic features was 2.0% (95% CI=1.9%-2.1%), with higher rates in women than in men. In all, 18.5% of the subjects who fulfilled the criteria for a major depressive episode had psychotic features. Past consultations for treatment of depression were more common in depressed subjects with psychotic features than in depressed subjects with no psychotic features. CONCLUSIONS: Major depressive episodes with psychotic features are relatively frequent in the general population, affecting four of 1,000 individuals. Feelings of worthlessness or guilt can be a good indicator of the presence of psychotic features.